The dot-com bubble, the Bush deficits, and the U.S. current account - Kraay, Aart 1995- (Policy research working paper, 2005)
"Over the past decade the United States has experienced widening current account deficits and a steady deterioration of its net foreign asset position. During the second half of the 1990s, this deterioration was fueled by foreign investment in a booming U.S. stock market. During the first half of the 2000s, this deterioration has been fuelled by foreign purchases of rapidly increasing U.S. government debt. A somewhat surprising aspect of the current debate is that stock market movements and fiscal policy choices have been largely treated as unrelated events. Stock market movements are usually interpreted as reflecting exogenous changes in perceived or real productivity, while budget deficits are usually understood as a mainly political decision. The authors challenge this view here and develop two alternative interpretations. Both are based on the notion that a bubble (the "dot-com" bubble) has been driving the stock market, but differ in their assumptions about the interactions between this bubble and fiscal policy (the "Bush" deficits). The "benevolent" view holds that a change in investor sentiment led to the collapse of the dot-com bubble and the Bush deficits were a welfare-improving policy response to this event. The "cynical" view holds instead that the Bush deficits led to the collapse of the dot-com bubble as the new administration tried to appropriate rents from foreign investors. The authors discuss the implications of each of these views for the future evolution of the U.S. economy and, in particular, its net foreign asset position. "--World Bank web site